Effect of Caffeine on Motility of Epididymis Spermatozoa of Bali Bull in Slaughterhouse Cibinong - Oktora Dwi Putranti; Lovita Adriani; S. Soeparna; Tita Damayanti Lestari (Chalaza Journal of Animal Husbandry, 2019)
Abattoir is the place to get meat but also a source of potential genetic sperm. Sperm from a slaughterhouse has low motility. Sperm motility can be improved by adding caffeine to the thinner before being used for fertilization. Caffeine is an alkaloid compound that can increase energy through a cAMP cycle. The method used is the testis of 12 cows Bali taken from a slaughterhouse Cibinong and do frozen sperm. Frozen sperm is analyzed using a computer-assisted sperm Analyzed (CASA) who had been treated caffeine 0, 2, 4, and 6 mg/ml. Fertility frozen epididymis sperm was tested using in vitro fertilization. Results were analyzed using a completely randomized design (CRD) with four treatments unidirectional pattern three repetitions. The results showed that the treatment with the addition of caffeine to the thinner of the yolk tris egg yolk epididymis sperm, there was no difference in motility, recovery rate, Curvilinear velocity (VCL), average path velocity (VAP), and straight-line velocity (VSL).